Relationship Between Weight Status and Health-Related Quality of Life in School-age Children in China - Mandana Zanganeh; Peymané Adab; Bai Li; Miranda Pallan; Wei J. Liu; Lin Rong; Wei Liu; James Martin; Kar K. Cheng; Emma Frew (Journal of Health Economics and Outcomes Research)
**Background:** Some studies from high-income countries suggest that overweight and/or obesity in children are negatively associated with health-related quality of life (HRQOL). However, the relationship between weight status and HRQOL is not well established in China, where obesity trends follow a different pattern compared with high-income countries. The risk of obesity is greater in children from higher socioeconomic backgrounds and higher in boys compared with girls.